Combined protein and calcium β-hydroxy-β-methylbutyrate induced gains in leg fat free mass: a double-blinded, placebo-controlled study - Alexander C. Stahn; Martina Anna Maggioni; Hanns-Christian Gunga; Elmarie Terblanche (Taylor & Francis Group, 2020)
Background The leucine metabolite β-hydroxy-β-methylbutyrate (HMB) is widely used as an ergogenic supplement to increase resistance-training induced gains in fat free mass (FFM) and strength in healthy adults. Recent studies have questioned the effectiveness of HMB, particularly when a high protein diet is habitually consumed. To investigate the additive resistance-training induced effects of HMB and protein in untrained individuals, we conducted a randomized double-blind, placebo-controlled study that compared the effects of combined protein and HMB supplementation to protein supplementation alone on FFM and muscle strength after 12-week resistance training. Methods Sixteen healthy men (22 ± 2 yrs) performed a periodized resistance-training program for twelve weeks (four sessions per week). The program comprised two mesocycles, characterized by a linear periodization and non-linear periodization, respectively, and separated by a 1-week tapering period. All participants received 60 g of whey protein on training days and 30 g of whey protein (WP) on non-training days. Participants were randomly assigned to additionally receive 3 g of calcium HMB (WP + HMB) or a placebo (WP + PLA). Body composition and physical fitness were tested before and after the 12-week training program. Whole-body and arm and leg fat free mass (FFM) were assessed by bioimpedance spectroscopy; upper arm and leg fat free cross sectional areas were also quantified using magnetic resonance imaging (MRI); upper and lower body strength were measured by One-repetition maximum (1-RM) bench press and leg press. Results Whole-body and segmental FFM increased in both groups (P <  0.001). However, gains in leg FFM were higher in WP + HMB vs. WP + PLA (arm FFM: + 6.1% vs. + 9.2%, P = 0.2; leg FFM: + 14.2% vs. + 7.0%, P <  0.01). No change in fat mass was observed (P = 0.59). 1-RM increased in both groups (P <  0.001). Conclusions Combined protein and HMB supplementation resulted in segmental, but not whole-body increases in FFM compared to protein supplementation alone. These findings could explain some of the controversial effects of HMB reported in previous studies and have practical implications for maximizing training-induced gains in FFM and clinical conditions associated with skeletal muscle deconditioning such as aging, sedentary lifestyles, bed rest and spaceflight.